Language of the Mass Media As An Object of Interdisciplinary Research - NURKEEVA B.A., (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
The article is devoted to the analysis of the modern linguistic situation. The main factors influencing the development of the modern literary language are identified, among which the central place belongs to the language of the media. The prospects and nature of the development of the modern Russian literary language are characterized.